New directions in linear acoustics and vibration : quantum chaos, random matrix theory, and complexity - Wright, M. C. M. (Matthew C. M.); Weaver, Richard, 1949- (Cambridge University Press, 2010)
"Linear acoustics was thought to be fully encapsulated in physics texts of the 1950s, but this view has been changed by developments in physics during the last four decades. There is a significant new amount of theory that can be used to address problems in linear acoustics and vibration, but only a small amount of reported work does so. This book is an attempt to bridge the gap between theoreticians and practitioners, as well as the gap between quantum and acoustic. Tutorial chapters provide introductions to each of the major aspects of the physical theory and are written using the appropriate terminology of the acoustical community. The book will act as a quick-start guide to the new methods while providing a wide-ranging introduction to the physical concepts"--Provided by publisher